SELIMUT ANTI API INOVASI PENCEGAHAN DAN MITIGASI KEBAKARAN TAHAP AWAL BERSAMA MITRA PBKM KESUMA MARELAN MEDAN - Suyanti, Retno Dwi; Pardosi, Sri Masnita; Nasution, Alvi Sahrin; Prima, Heppy Setya (Jurnal Abdi Insani, 2025)
Fires are sudden disasters that can cause significant losses, both material and non-material. Prompt early response is crucial to prevent the spread of fire, but many communities lack simple and easy-to-use fire extinguishers. A five-member community service team, in collaboration with the Kesuma Community Learning Center (PKBM), led by Ms. Siti Nurhayati, located in Lk 2 Pasar 2 Barat Terjun, Medan Marelan, and involving 40 community members as partners, conducted training and developed an innovation called a "Fulerene Patterned Fire Blanket." This blanket is made from heat-resistant fullerene-patterned fiberglass and coated with sodium bicarbonate (NaHCO₃), which accelerates fire extinguishing by lowering the temperature and inhibiting oxidation. This combination of materials results in a device that is high-temperature resistant, lightweight, and reusable after washing. This activity included outreach, demonstrations, hands-on training, and involved the local community in simple production of the device. The results demonstrated an increase in community knowledge and skills in dealing with small fires. Enthusiasm for this safe and economical design has also increased disaster awareness and preparedness at the community level. The positive response has opened up opportunities for broader program development. Scientific studies have shown that fullerene-patterned fire blankets are effective as a preventative solution, enhancing community preparedness for early fire risks.